Osteogênese de células-tronco humanas em matriz tridimensional de poli-3-hidroxibutirato- co-3-hidroxivalerato utilizando meio suplementado com soro humano - Ana Claudia Chagas de Paula (2011)
Tissue Engineering is a multidisciplinary science that offers a strategy to circumvent the major problems related with bone regenerative and therapeutic procedures. In its context, the human adipose stem cells (hASC) are an attractive and abundant cell source to be cultured in scaffolds under specifics factors stimulus. An ex vivo expansion of these cells is necessary before clinical application and currently, cell culture medium use fetal calf serum (FCS). However, animal serum is not a safety supplement for culture medium, raising the risk of trigger severe immune response and transmission of pathogenic microorganisms to the recipient. So the challenge is to establish standard and reliable cell culture medium. Therefore, the aim of this study is evaluate the possibility of using a pool of allogeneic human serum (allo HS) rather than FCS as supplement of the culture medium for hASC. As well as seeding these cells on poly-3-hydroxybutyrate-co-3-hydroxyvalerate (PHB-HV) scaffolds, developed by freeze drying technique, in order to be used in bone tissue engineering field. The results showed that hASC cultured in DMEM supplemented with allo HS had an increased proliferation but maintained the immunophenotype characteristic for mesenchymal stem cell and the cells were capable of differentiate into osteogenic lineage. The scaffolds of PHB-HV developed showed an adequate structure allowing adhesion and proliferation of hASC. Moreover the hASC were capable of differentiate into osteogenic lineage. All these results indicate that allo HS may be a promising supplement for ex vivo expansion and differentiation medium of hASC and the PHB-HV scaffolds associated with hASC and medium supplemented with allo HS and osteogenic factors are suitable to induce bone formation. At first, this construct seems useful and safety to bone tissue engineering.